Implementation of Fisher-Yates Shuffle and Fuzzy Tsukamoto in Nusantara Educational Game - Khairul Insan Karim; Chairunnisa Lamasitudju; Ryfial Azhar; Fizar Syafaat; Anisa Yulandari (Journal of Applied Informatics and Computing)
This research introduces "PINUS: Petualangan Ilmu Nusantara," an educational game designed to improve players' knowledge and interest in Indonesian culture, flora, fauna, and national figures. The game incorporates the Fisher-Yates Shuffle algorithm to randomize questions and answers, ensuring variety, and the Fuzzy Tsukamoto algorithm to calculate scores based on player performance for fair and competitive assessment. Quantitative methods were employed, with data collected through interviews, literature reviews, and system testing via alpha testing (black- box) and beta testing (user acceptance testing or UAT). The One Group Pretest- Posttest Design method was also applied. The findings show that the Fisher-Yates Shuffle enhances challenge and engagement, while the Fuzzy Tsukamoto algorithm ensures balanced scoring, fostering motivation. UAT results indicate strong functional acceptance, with an average score of 84.9% ("Strongly Agree"). The pre- test and post-test analysis revealed a score improvement average of 0.307, categorized as moderate. These findings affirm PINUS effectiveness in enhancing learning comprehension by offering interactive features, educational content, and dynamic question variations. The game provides an engaging, accessible, and technology-driven learning medium, making it a valuable tool for supporting educational initiatives.